2019
DOI: 10.1021/acs.jproteome.8b00647
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomic Analysis of Small and Large Extracellular Vesicles (EVs) Reveals Enrichment of Adhesion Proteins in Small EVs

Abstract: Extracellular vesicles (EVs) are important mediators of cell-cell communication due to their cargo content of proteins, lipids and RNAs. We previously reported that small EVs (SEVs) called exosomes promote directed and random cell motility, invasion, and serum-independent growth. In contrast, larger EVs (LEVs) were not active in those assays, but may have unique functional properties. In order to identify protein cargos that may contribute to different functions of SEVs and LEVs, we used isobaric tag for relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 118 publications
(231 reference statements)
3
70
1
Order By: Relevance
“…Quality aspects of the derived EVs include the following: size distribution (by nanoparticle tracking analysis), protein concentration (by Western blot, proteomics), transmission electron microscopy, flow cytometry (with antibody-coated beads), proteomics, 51 and miRNA profiling. 52 For example, small EVs were found to be enriched in proteins associated with cell-cell junctions, cell-matrix adhesion, exosome biogenesis machinery, and various signaling pathways.…”
Section: Ev Characterizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quality aspects of the derived EVs include the following: size distribution (by nanoparticle tracking analysis), protein concentration (by Western blot, proteomics), transmission electron microscopy, flow cytometry (with antibody-coated beads), proteomics, 51 and miRNA profiling. 52 For example, small EVs were found to be enriched in proteins associated with cell-cell junctions, cell-matrix adhesion, exosome biogenesis machinery, and various signaling pathways.…”
Section: Ev Characterizationsmentioning
confidence: 99%
“…In contrast, large EVs were enriched in proteins associated with ribosome and RNA biogenesis, processing, and metabolism. 51 As a general rule, at least three or more categories of EV-specific markers and non-EV-specific proteins should be measured semiquantitatively. 53,54 For preclinical and clinical studies of EV therapy, several types of assays need to be performed: (1) fingerprint assays, to provide quality control using a narrowly defined set of surrogate markers for EVs; (2) potency assays, to determine which cells are activated by EVs and to what extent; (3) mechanistic assays, important to establish positive and negative controls for fingerprint and potency assays; and (4) safety testing, such as biodistribution patterns, cytotoxicity, and pharmacokinetics.…”
Section: Ev Characterizationsmentioning
confidence: 99%
“…We have also found that the adhesion of MDA-MB-231 cells to tissue culture plates was aided by SEVs but not by LEVs, which lack αvβ3 integrin and FN; both molecules were detected only in SEVs. Previous reports described the ability of tumor derived EVs in promoting tumor cell adhesion [33,34]. Also, the role of EV-αvβ3 integrin in platelets adhesion has been demonstrated [59].…”
Section: Discussionmentioning
confidence: 95%
“…Integrins carried on SEVs have been shown to support tumor spread and metastasis development [18,[29][30][31][32][33] while exosomes mediate cell adhesion to matrix components [34,35]. In addition, α5β1 integrin found on exosomes was shown to bind fibronectin and promote cancer cell adhesion and motility [36].…”
mentioning
confidence: 99%
“…Remarkably, SW480-and SW620-sMVs displayed distinct signatures; SW480-sMVs was enriched in ITGA/B, ANXA1, CLDN7, CD44, and EGFR/NOTCH signaling networks, while SW620-sMVs are higher in PRKCA, MACC1, FGFR4, and MTOR/MARCKS signaling networks. Jimenez et al evaluated the proteins in small and large extracellular vesicles (SEVs and LEVs, respectively) [128], applying isobaric tag for relative and absolute quantitation liquid chromatography (iTRAQ-LC) [87] tandem mass spectrometry (MS) on EVs from colon cancer cell line (SW-480) and the lymph node metastatic line (SW-620) and a CRC patient primary culture. Bioinformatic analyses showed that SEVs contain higher levels of proteins involved in cell-cell junctions, cell-matrix adhesion, exosome biogenesis, and diverse signaling pathways and that LEVs contain higher levels of proteins associated with the biogenesis of ribosomes and RNA biogenesis and processing and with metabolism.…”
Section: Applications Of Ms In Colorectal Cancermentioning
confidence: 99%